ANALISIS ANGGARAN PARSIAL DAN PREFERENSI PETANI TERHADAP KARAKTER BEBERAPA VARIETAS UNGGUL PADI LAHAN SAWAH TADAH HUJAN DI KABUPATEN SAMBAS (STUDI KASUS DESA MATANG DANAU, KEC.PALOH) - Burhansyah, Rusli (Jurnal Social Economic of Agriculture, 2019)
Problems with rainfed lowland rice cultivation in Sambas Regency include; the level of productivity is still low and the attack of blast disease and planthopper pests. Therefore, the introduction of new high-yielding varieties that have high productivity and resistant to blast disease and planthopper pests. Besides that, new improved varieties are in accordance with the tastes of the local community. This study aims to determine the analysis of the financial feasibility and preferences of farmers to the character of superior varieties of rice in rain-fed rice fields. The field research was carried out on 10 hectares of farmers' land and survey in Matang Danau village, Paloh sub-district. Research time is from April to August 2018. Respondents were 30 ethnic Malay cooperative farmers. Data collected included input and output data of rice farming, farmer characteristics, plant morphology. Data collection through observation and interviews with farmers. Observations were made on growth in the field and just before harvest. From the results of the study showed that the new superior variety of Inpari 41 was feasible to be cultivated with MBCR 1.49 with additional gross revenue of Rp 5,435,000 (39.92%) with again on the total cost of Rp 1,252,940 (22.45%) of the variety Cilosari. Farmers like the Inpari 41 variety because based on plant type, plant height, panicle length, number of productive tillers, level of production, resistance to pests and diseases, grain loss rate, grain color, aspects that get attention in developing rice in rainfed lowland are vegetative growth, grain form, quality of rice, rice texture, and taste of rice that are favored by local farmers as information for breeders in assembling new superior varieties of rainfed lowland rice.Â Keywords: Financial feasibility, Preference, New high yielding varieties, Rainfed lowland